RELIGION AND CULTURE THE PERSPECTIVE OF CUSTOMARY LAW IN THE WEDDING TRADITION OF SASAK SOCIETIES IN LOMBOK - Rusdi Abadi Siregar; Orien Effendi (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
Maintaining local wisdom values or traditional values of a culture in the midst of modernization of people's lives today is very important, in addition to providing messages and educational values to the next generation it also has meaning as evidence of history or civilization of human life.Â This research on cultural values in the tradition of the Lombok community's wedding procession highlights at least three things including; the influence of modernization on the sustainability of culture or tradition, the influence of modernization on the meaning of conveying moral messages and cultural values, and analyzing the shift in cultural values from the perspective of moderate Islam. This research uses a qualitative method. Collecting data by observation, interview, and documentation. The results of this study indicate that the tradition of the Lombok community's wedding procession still exists today, but some of the processions or rituals in it have shifted and lost their traditional values, as well as the meaning of conveying the message of the tradition has been scratched because of the bad influence due to the change of some rituals with their sacred characteristics towards modern